Unmasking Desire and Morality: A Feminist-Psychoanalytic Analysis of Gender Roles, Power, and Beauty Ideals in Snow White and the Seven Dwarfs (1937) - Sharenlie, Grania; Hutahayan, Elizabeth Xaviera Gaylene; Purnama, Aurellia Zureil; Paat, Cinzia Pingkan Abigail; Rustandar, Evan Denzel (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
This study aims to view the different gender portrayals of females in society from the film “Snow White and the Seven Dwarfs (1937)”. In the point of view of patriarchal society, the females are often depicted as passive and innocent individuals. By using the qualitative method and Feminist-Psychoanalysis framework by Gilbert, S. M., & Gubar, S. (1979), this research investigated the idealization of women and different treatment of men and women. The analysis of the film, as the primary object of study, involves close examination of its cinematography and dialogue to enrich the data. As a result: 1) Snow White and the Evil Queen represent contrasting attitudes of women in the patriarchal society and get different treatment by the men. 2) The ideal beauty of Snow White intimidates the Evil Queen’s jealousy, leading to a mother-daughter conflict. 3) The different treatment of men and women contributes to the shaping of female trauma through the character's past events. This analysis highlights the reality of how females are often treated and how societal norms frequently frame women identity based and appearance and personality. Understanding this dynamic is important to recognize that women are always treated differently. Hopefully, this study would enhance the study of feminism and encourage further research into these critical issues. Future research could explore more whether they uphold or challenge old gender ideas. It would also be valuable to study how today's viewers understand the film's gender roles and beauty standards.